Effectiveness of Direct Pulp Capping Bioactive Materials in Dentin Regeneration: A Systematic Review - Ermin Nie (MDPI AG, 2021)
Background: Regenerative endodontics aims to restore normal pulp function in necrotic and infected teeth, restoring protective functions, such as innate pulp immunity, pulp repair through mineralization, and pulp sensibility. The aim of this systematic review was to assess the dentin regeneration efficacy of direct pulp capping (DPC) biomaterials. Methods: The literature published between 2005 and 2021 was searched by using PubMed, Web of Science, Science Direct, Google Scholar, and Scopus databases. Clinical controlled trials, randomized controlled trials, and animal studies investigating DPC outcomes or comparing different capping materials after pulp exposure were included in this systematic review. Three independent authors performed the searches, and information was extracted by using a structured data format. Results: A total of forty studies (21 from humans and 19 from animals) were included in this systemic review. Histological examinations showed complete/partial/incomplete dentin bridge/reparative dentin formation during the pulp healing process at different follow-up periods, using different capping materials. Conclusions: Mineral trioxide aggregate (MTA) and Biodentine can induce dentin regeneration when applied over exposed pulp. This systematic review can conclude that MTA and its variants have better efficacy in the DPC procedure for dentin regeneration.